Efektivitas Partisipasi Perempuan Pada Pendidikan Non Formal di Pusat Kegiatan Belajar Masyarakat (PKBM) Kecamatan Wedarijaksa Kabupaten Pati - Abdul Karim (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
This study aimed to get an overview of strategies to develop women’s participation in non-formal education through the Community Learning Center (Pusat Kegiatan Belajar Masyarakat-PKBM) and the effectiveness of their participation in family and community life. Explorative study used a qualitative approach to obtain field data as well as the clarity of the object that is the focus of the study. The results showed that the effectiveness of women’s participation in non-formal education in the PKBM is done through group learning with participatory approaches. The result gives a positive change towards the formation of attitudes and behaviors such as the ability to manage time for activities, foster self-confidence and can provide income.